The Offer Framing Effect: Choosing Single versus Bundled Offerings Affects Variety Seeking. Issue 4 (8th September 2014) - Mittelman, Mauricio; Andrade, Eduardo B.; Chattopadhyay, Amitava; Brendl, C. Miguel
Abstract : Choices of multiple items can be framed as a selection of single offerings (e.g., a choice of two individual candy bars) or of bundled offerings (e.g., a choice of a bundle of two candy bars). Four experiments provide strong evidence that consumers seek more variety when choosing from single than from bundled offerings. The offer framing effect shows that the mechanics of choosing—the ways consumers go about making choices of multiple items—affect variety seeking in a systematic manner. The data also suggest that the effect is largely due to the single offering frame. Theoretical and managerial implications are discussed.